Structural and inhibitory effects of fulvic and humic acids against tyrosinase. Issue 10 (21st June 2022) - Taherkhani, Negar; Hekmat, Azadeh; Piri, Hossein; Haghbeen, Kamahldin
Abstract: Inhibition of tyrosinase activity can control fruit browning and preserve the flavor and nutritional value of food. The impacts of fulvic acid (FA) and humic acid (HA) on tyrosinase activity were investigated utilizing circular dichroism (CD) and fluorescence spectroscopy, molecular docking (MD), and molecular dynamics simulations. HA and FA demonstrated a mixed type of inhibition with K i 2.02 and 5.2 μM, respectively. The thermodynamic parameters displayed that the hydrogen bond and hydrophobic force play a major role in the FA‐tyrosinase and HA‐tyrosinase interaction, respectively. Fluorescence experiments demonstrated changes in tyrosinase tertiary structures. HA could not destroy the tyrosinase secondary structure significantly, however, FA has a significant influence on the tyrosinase secondary structure. The molecular dynamics findings demonstrated the minimal fluctuations and the lowest flexibility in the complex amino acids in the HA‐tyrosinase and FA‐tyrosinase interaction. Altogether, HA and FA could be utilized in food industries as an accessible natural source for tyrosinase inhibition. Practical applications: Recently, the investigation of tyrosinase inhibitors from the biosphere for hindrance of undesired browning in the food industry has increased considerably. Mushroom tyrosinase is a suitable model for kinetic research owing to its availability as well as close conformational similarity to tyrosinase in a mammal. Natural sources and their effective compounds could have wonderful potential on tyrosinase activity and structure, thus, in this study, the interactions between tyrosinase and fulvic acid (FA) and Humic acid (HA) were investigated. Previously, it has been shown that HA and FA have antioxidant properties and they can improve the quality of food via retarding lipid oxidation. Altogether, further investigations are warranted to draw firm conclusions, HA and FA could be utilized in food industries not only as antioxidant agents but also as an accessible natural source for tyrosinase inhibition. Abstract : Humic acid and Fulvic acid demonstrated a mixed type of inhibition. The hydrophobic force and hydrogen bond play a major role in the humic acid‐tyrosinase and fulvic acid‐tyrosinase interaction, respectively. The MD findings demonstrated the lowest flexibility in the complex amino acids and minimal fluctuations in the humic acid‐tyrosinase and fulvic acid‐tyrosinase interaction.